Analysis of Service Quality Issues in J&T Express Using Check Sheets, Pareto Chart, and Fishbone Diagram - Desty Hapsari Kirana; Abyan Yaskur Mulki; Jevon Monahan Tulus Sidabutar (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2026)
This study investigates the recurring service quality issues at J&T Express, a prominent logistics company in Indonesia. The rapid growth of the logistics industry, fueled by the rise in online shopping, has resulted in significant challenges in maintaining service quality. Frequent customer complaints, such as lost packages, damaged goods, wrong deliveries, and poor response to inquiries, were identified through customer feedback on various online platforms. To address these issues, the study employs quality management tools including check sheets, Pareto charts, and fishbone diagrams. Check sheets were used to systematically record customer complaints and identify the most frequent issues. The Pareto chart, based on the 80/20 principle, highlighted that a small number of issues, such as lost packages, contributed significantly to the overall complaints. The fishbone diagram helped in identifying the root causes of these problems, uncovering issues in areas such as technology, human resources, operational processes, materials, and environmental factors. Based on the analysis, the study proposes targeted recommendations for improving service quality at J&T Express. These recommendations include strengthening tracking systems, enhancing customer service responsiveness, improving package handling procedures, and implementing standardized operational processes. The findings of this study contribute to the understanding of service quality management in the logistics sector and offer practical insights for companies looking to enhance customer satisfaction.